Agricultural markets in a transitioning economy [ an Albanian case study - Chan-Halbrendt, Catherine , 1949-; Fantle-Lepczyk, Jean (CABI, 2013)
This book focuses on the major challenges and opportunities facing agriculture sectors in the wake of the transition from a planned to a market economy and potential entry to the European Union. Using Albania as a case study, it examines the shift from centrally planned economy to free markets, and the lasting effects of such change on the agricultural sector. It also looks at the future of agriculture in transitioning economies and presents findings from recent academic research activities funded by the Albania/Hawaii Higher Education and Economic Development (AHEED) Project. A consistent theme throughout the text is the changing roles of universities and extension, and their importance to the future growth of economies such as that of Albania. The book has 12 chapters and a subject index.